Ventricular arrhythmia prevalence and treatment with omega-3 polyunsaturated fatty acids in patients who suffered myocardial infarction within the last year - N. G. Gogolashvili; M. V. Litvinenko; T. N. Pochikaeva; E. S. Vavitova; L. S. Polikarpov; N. Ya. Novgorodtseva (Кардиоваскулярная терапия и профилактика)
Aim. To study the prevalence of ventricular arrhythmias (VA) in the patients who suffered myocardial infarction (MI) within the last year; to evaluate the effects of the treatment with omega-3 polyunsaturated fatty acids (PUFA) for 6 months. Material and methods. In total,370 MI patients underwent 24-hour Holter monitoring of electrocardiogram (ECG), with the subsequent VA analysis by age and gender. Fifty six patients had 500-100 ventricular extrasystoles (VE) registered in 24 hours. Group I (n=30) received omega-3 PUFA (1 g/d) for 6 months; Group II patients (n=26) were controls.Results. In patients with VA, the mean number of VE reached 374,6. The daily VE number increased with age: from 185,4 in people aged 30-59 years to 574,3 in participants aged 60 years or older (р=0,002). In men aged ≥60 years, the daily VE number was greater than in men aged 30-59 years (р=0,001). After 6 months of the omega-3 PUFA treatment, Group I demonstrated reduced prevalence of all VE (from 699 to 139; р=0,004), as well as a decrease in the percentage of frequent VE (from 93,3 % to 40 %; р=0,00001), paired VE (from 83,3 % to 46,7 %; р=0,003), Grade 4B VE (from 50 % to 20 %; р=0,02), and all high-grade (3-5) VE (from 83,3 % to 50 %; р=0,006). No positive dynamics was observed for the control Group II. Conclusion. In most patients who suffered MI within the last year, the prevalence of VE was relatively low. The VA prevalence and daily VE number increased with age, both in all examined patients and in men only. In women, advanced age was linked to an increased VA prevalence. Omega-3 PUFA treatment for 6 months was associated with a reduction in the daily VE number and the prevalence of Grade 2, 3, 4A, 4B, and all high-grade VE. In the controls, the prevalence of Grade 4B VE increased.